1991
DOI: 10.21273/hortsci.26.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency Inhibits Chlorophyll Synthesis and Gas Exchange in `Stuart' Pecan

Abstract: Leaves of `Stuart' pecan [Carya illinoensis (Wangenh.) C. Koch] with various levels of Zn deficiency were analyzed for physiological indicators of leaf vigor. Leaf chlorophyll content, stomatal conductance, and net photosynthesis were adversely affected by Zn deficiency. In leaves with severe Zn deficiency, each of these indicators increased 3- to 5-fold with a doubling of leaf Zn concentration, but stabilized as leaf Zn approached the sufficiency range (14 μg·g-1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 14 publications
7
39
1
Order By: Relevance
“…There have been previous reports of zinc deficiency causing a reduction in g s (e.g. in pecan; Hu and Sparks, 1991). Zinc may be involved in stomatal regulation due to its role in maintaining membrane integrity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There have been previous reports of zinc deficiency causing a reduction in g s (e.g. in pecan; Hu and Sparks, 1991). Zinc may be involved in stomatal regulation due to its role in maintaining membrane integrity.…”
Section: Discussionmentioning
confidence: 97%
“…Sharma et al (1984), for example, reported that zinc deficiency in cabbage lowered osmotic potential and increased water saturation deficit compared to plants grown with an adequate supply of zinc. Stomatal conductance and transpiration rates also declined under zinc deficiency (Hu and Sparks, 1991;Sharma et al, 1984Sharma et al, , 1994. Gas exchange data presented by Hu and Sparks (1991) and Sharma et al (1994) indicated that zinc deficiency causes a reduction in the instantaneous transpiration efficiency of leaves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Mn is a critical component of chloroplasts, specifically benefiting photosystem II (Teichler-Zallen 1969), and so should also be critical in photosynthetic C gain. One of the major impacts of Zn deficiency is decline in chlorophyll production and photosynthetic rates (Hu and Sparks 1991). Although the role of B in plants is uncertain (Blevins and Lukaszewski 1994;Bolaños et al 2004), it is likely that B plays a role in plant cell membranes (Blevins and Lukaszewski 1998;Lehto et al 2010), and it appears that B fertilization leads to increased EcMF colonization (Mitchell et al 1987(Mitchell et al , 1990Lehto et al 2004Lehto et al , 2010.…”
Section: Thelephora Terrestrismentioning
confidence: 99%
“…In cabbage, Zn deficiency lowered osmotic potential and increased water saturation deficit (Sharma et al 1984(Sharma et al , 1994. The transpiration rate (E) of pecan plants declined under Zn deficiency (Hu and Sparks 1991). Grewal and Williams (2000) showed that the ability of alfalfa plants to cope with water stress during early vegetative stage could be enhanced with adequate Zn supply.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%